Analysis of SIRT1 genetic variants in young Mexican individuals: relationships with overweight and obesity - Salazar-García, S.; Ibáñez-Salazar, A.; Lares-Villaseñor, E.; Gaytan Pacheco, Noemi; Uresti-Rivera, E.; Portales-Pérez, D. P.; De la Cruz-Mosso, U.; Vargas-Morales, J. M. (Frontiers in Genetics, 2024)
The high prevalence of obesity in Mexico starting from the early stages of life is concerning and represents a major public health problem. Genetic association studies have reported that single nucleotide variants (SNVs) in SIRT1, an NAD+-dependent deacetylase that plays an important role in the regulation of metabolic cellular functions, are associated with multiple metabolic disorders and the risk of obesity. In the present study, we analyzed the effect that the SNVs rs1467568 and rs7895833 of the SIRT1 gene may have on cardiometabolic risk factors in a young adult population from Mexico. A cross-sectional study was carried out with young adults between the ages of 18 and 25 who had a body mass index (BMI) greater than 18.5 kg/m2. This study included 1122 young adults who were classified into the normal weight (n=731), overweight group (n=277), and obesity group (n=114) according to BMI of whom 405 and 404 volunteers were genotyped for rs1467568 and rs7895833 respectively using TaqMan probes through allelic discrimination assays. We found that the male sex carrying the G allele of rs7895833 had slightly lower BMI levels (p = 0.009). Furthermore, subjects carrying rs1467568 (G allele) showed a 34% lower probability of presenting with hyperbetalipoproteinemia where female carrying rs1467568 had lower levels of total cholesterol (p = 0.030), triglycerides (p = 0.026) and LDL cholesterol (p = 0.013). In conclusion, these findings suggest that the presence of both SNVs could have a non-risk effect against dyslipidemia in the Mexican population. Key words: SIRT1, Obesity, Single nucleotide variants, Genetic association, BMI